Community Service Through The Indonesian Red Cross Volunteer Corps (KSR PMI) Unit at Universitas Haji Sumatera Utara, Fifth Cohort - Damanik, Balqis Nurmauli; Anwar, Syahferi (IKHLAS: Jurnal Pengabdian Dosen dan Mahasiswa, 2024)
This community service program was conducted by the Indonesian Red Cross Volunteer Corps (KSR PMI) Unit at Universitas Haji Sumatera Utara in 2022, focusing on the 5th cohort. The initiative aimed to enhance students' practical skills in emergency response, disaster management, and health services while fostering social responsibility and community engagement. Through training and direct participation in humanitarian activities, students developed critical competencies in first aid, logistical support, and emotional care for disaster victims. The program also strengthened the bond between the university and the local community, contributing positively to societal well-being. This community service project not only provided immediate benefits to those in need but also enriched the students' educational experience, preparing them to be more empathetic and professional in real-world situations.